2019
DOI: 10.3390/sports7070164
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Muscle Power and Muscle Morphology with Different Volumes of Fast Eccentric Half-Squats

Abstract: The aim of the study was to evaluate power performance and muscle morphology adaptations in response to 5 weeks of fast-eccentric squat training (FEST) performed twice per week, with three different training volumes. Twenty-five moderately trained females were assigned into three groups performing eight repetitions of FEST of either four sets (4 × 8 group; N = 9), 6 sets (6 × 8 group; N = 8) or eight sets (8 × 8 group, N = 8). Before and after the intervention, countermovement jumping height (CMJh) and power (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In this context, the specificity of training would include fast eccentric only squats, where participants are instructed to “squat fast and stop rapidly at a half-squat position”, a modality shown in untrained subjects to induce greater adaptations to fast-twitch type IIX muscle fibres and explosive isometric RFD than slow eccentric-only squats [ 43 ]. Furthermore, these enhancements were also evident following low volume (4 × 8 reps, twice per week) interventions in moderately trained individuals [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the specificity of training would include fast eccentric only squats, where participants are instructed to “squat fast and stop rapidly at a half-squat position”, a modality shown in untrained subjects to induce greater adaptations to fast-twitch type IIX muscle fibres and explosive isometric RFD than slow eccentric-only squats [ 43 ]. Furthermore, these enhancements were also evident following low volume (4 × 8 reps, twice per week) interventions in moderately trained individuals [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the classical blood or saliva samples, that are usually collected before and several time points after the exercise trial this type of experiments allow you to take samples of the inflamed tissue, namely muscle biopsies. This technique has been used in many studies, investigating either the training-induced adaptations on muscle fibers (for example [ 89 , 122 , 257 , 258 , 259 , 260 , 261 , 262 , 263 ]), or muscle damage-inflammation (for example [ 63 , 122 , 128 , 231 , 248 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 ]. Muscle samples for such type of studies are usually obtained with Bergstrom needles from vastus lateralis of lower extremities, under local anesthesia, easy and quite safe for the volunteers, while in the majority of the countries, this is well accepted from the bioethics committees.…”
Section: Exercise-induced Muscle Damage and Its Methodological Advmentioning
confidence: 99%
“…For example, it has been reported that in a world champion shot putter, with a predominance of type I muscle fibers (~60%), his hypertrophied type II muscle fibers occupied 67% of VL the area, making him able to achieve greater power and shot put performance, compared to another shot-putter with a predominance of type II fibers but with smaller type II fiber CSA [ 45 ]. Additionally, changes in the %CSA of muscle fibers seem to be linked with the accompanying changes in power performance [ 28 , 38 , 44 , 46 ]. The physiological background of muscle fiber %CSA importance in power performance is based on both, the properties of the large fibers, and of the mechanical characteristics of each fiber type.…”
Section: Discussionmentioning
confidence: 99%
“…1-RM Half Squat Strength. This test was performed according to the methodology previously described [ 10 , 28 , 32 , 33 , 38 ]. Thirty minutes after the end of the CMJ testing, maximal half-squat strength was assessed in a Smith squat rack.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation